The Effect of Amniotic Membrane Stem Cell Metabolite Product (AMSP-MP) Combine with Vitamin E after Microneedling in Photoaging Progress - Cita Rosita Sigit Prakoeswa; Agatha Anindhita Ayu Ardhaninggar; Riyana Noor Oktaviyanti; Irmadita Citrashanty; Maylita Sari; Menul Ayu Umborowati; Dwi Murtiastutik (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: The photoaging is a cumulative process. Amniotic Membrane Stem Cell Metabolite Products(AMSC-MP) that contain cytokines and growth factors that have a role in the skin’s rejuvenation process.Vitamin E is an antioxidant that has a photoprotective effect. Topical combination of AMSC-MP and VitaminE are expected to have an effect on clinical photoaging improvement.Objective: To evaluate the effect of topical combination of AMSC-MP with vitamin E after microneedlingcompared with AMSC metabolite products after microneedling.Methods: A total 60 photoaging women were included in this experimental analytic, controlled, matchingresearch. Each participant’s face was allocated to topical combination of AMSC-MP and vitamin E inintervention group and AMSC-MP only in control group. Microneedling modality was use to enhanceepidermal penetration. Three treatment sessions were repeated at two weeks’ interval.Results: From the comparison of the two groups showed there were significant different of mean value inwrinkle, skin tone and UV spots with p-value < 0,005 in the intervention grup. While pore and polarized spotdo not show significant differences between two groups.Conclusion: The administration of a topical combination of MP-AMSC and vitamin E after microneedlingprovides clinical improvement in photoaging.